2007
DOI: 10.1111/j.1447-0756.2007.00568.x
|View full text |Cite
|
Sign up to set email alerts
|

Blue rubber bleb nevus syndrome: Report of a patient with hemangiomas of the vaginal portion of the cervix appearing during pregnancy

Abstract: Blue rubber bleb nevus syndrome (BRBNS) is a rare disorder showing venous malformations in the skin and gastrointestinal tract, and other internal organs. We encountered a patient with BRBNS in whom hemangiomas of the uterine cervix appeared during pregnancy. This was apparently the first reported occurrence. To avoid unexpected bleeding from hemangiomas, patients with BRBNS should be examined repeatedly for hemangiomas of the birth canal, and special care should be taken in deciding the mode of delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 6 publications
0
25
0
2
Order By: Relevance
“…However, the cervical haemangioma can be treated, if necessary, by hysterectomy [15,18,20]. Spontaneous regression of the lesion has been reported by Tanaka et al [17]. The uterine cervix cavernous haemangioma is a rare lesion given its localization.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the cervical haemangioma can be treated, if necessary, by hysterectomy [15,18,20]. Spontaneous regression of the lesion has been reported by Tanaka et al [17]. The uterine cervix cavernous haemangioma is a rare lesion given its localization.…”
Section: Discussionmentioning
confidence: 99%
“…Tanaka [17] 2007 The Patient has BRBNS, haemangioma of the uterine cervix appeared during pregnancy. Caesarean section was performed without complications, One month after delivery, cervical haemangiomas were found to have decreased in size.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8 Tanaka et al reported spontaneous regression of the lesion. 9 The diagnosis of cavernous haemangioma is histological. Histologically mass is shapely defined and not encapsulated and composed of large cavernous blood filled vascular spaces separated by modest connective tissue stroma.…”
Section: Discussionmentioning
confidence: 99%